A Stieglerianesque Critique of Transhumanism: On Narratives and Neganthropocene - Mróz, Adrian (Hybris, 2019)
While drawing from the philosophy of Bernard Stiegler throughout the paper, I commence by highlighting Zoltan Istvan’s representation of transhumanism in the light of its role in politics. I continue by elaborating on the notion of the promise of eternal life. After that I differentiate between subjects that are proper for philosophy (such as the mind or whether life is worth living) and science (measurable and replicable). The arguments mostly concern mind-uploading and at the same time I elaborate on a simple critique of mind-body dualism, which is one of the key imagined orders exploitable by technologies in the narratives of transhumanism present in popular culture. This is reframed as a problem of action. The focus of this article is on the claim that certain transhumanisms are dangerous forms of Neo-Darwinism. It comes from a critical assessment of capital and the exploitation of bodies through market forces. Entropy is a process of growing disorder, while neganthropy is an anthropological struggle against exploitation, not only of bodies, but of all ecosystems of the Earth. The arguments of Stiegler from a collection of lectures are recapitulated, and his claims are presented through the prism of transhuman narrative, with a particular focus on Christian Salmon's position in the book Storytelling: Bewitching the Modern Mind.